Highly Selective Synthesis of Chlorophenols under Microwave Irradiation - Yawen Xiong; Hongdong Duan; Xia Meng; Zhaoyun Ding; Weichun Feng (Journal of Chemistry)
Oxychlorination of various phenols is finished in 60 minutes with high efficiency and perfect selectivity under microwave irradiation. These reactions adopt copper(II) chloride (CuCl2) as the catalyst and hydrochloric acid as chlorine source instead of expensive and toxic ones. Oxychlorination of phenols substituted with electron donating groups (methyl, methoxyl, isopropyl, etc.) at ortho- and meta-positions is accomplished with higher conversion rates, lower reaction time, and excellent selectivity. A proposed reaction mechanism is deduced; one electron transfers from CuCl2 to phenol followed by the formation of tautomeric radical that can be rapidly captured by chlorine atom and converts into para-substituted product.